The Role of Mungbean (Phaseolus radiatus) as a Fat Replacer on the Physicochemical Properties of Ice Cream - Nugroho, Pulung; Hartayanie, Laksmie; Dwiana, Kartika Puspa (Indonesian Journal of Agricultural Research, 2019)
Fat replacer can be an alternative in the processing of making ice cream. The use of fat replacers can replace the role of fat as forming texture, flavor, and aroma without reducing the quality of the ice cream. In this research, green beans we used as a fat replacer as a substitution to whipped cream. Mung beans are a high source of protein and carbohydrates. The purpose of this study was to determine the physicochemical characteristics of ice cream with the addition of mung bean flour and determine the optimal ratio of whipped cream optimal and mung bean as a fat replacer. Based on the results of research that has been done ice cream with a ratio of green bean flour: whipped cream (50: 50) has the best quality with a fat content of 7.74%, overrun 78.13%, hardness 17.46 kgf, viscosity 1170 cP.S, melting time is 49.17 minutes. It was concluded that the best ice cream was produced from addition of 25% and 50% green bean flour.